Spatial variation, environmental risk and biological hazard assessment of heavy metals in surface sediments of the Yangtze River estuary - Wang, Haotian; Wang, Jiawei; Liu, Ruimin; Yu, Wenwen; Shen, Zhenyao (Marine pollution bulletin, 2015)
•Environmental and biological hazard risk were assessed by geostatistics and GIS.•Anthropogenic inputs and fine grained sediments might explain for high enrichment.•Arsenic was defined as main pollutant in the Yangtze River estuary.•The contamination degree would be assessed by the combination of heavy metals. 30 samples of eight heavy metals were collected in February 2011 within Yangtze River estuary (YRE). The mean concentrations met the primary standard criteria based on Marine Sediments Quality of China. The spatial distribution showed that a gradient concentration decreased gradually from inner-estuary to river mouth. Anthropogenic inputs might be the main contributor, and fine grained sediments might also aggravate the heavy metal contamination. The assessment results indicated that the YRE was in low risk of contamination caused by every single heavy metal. However, it was in considerable degree of contamination considering combination of all the heavy metals. The toxicities of heavy metals might be elevated when heavy metals were in combination. Arsenic should be of primary concern due to its higher assessment values and the potential of adverse biological effects. And the concentration of As in the YRE had a trend to increase because of anthropogenic activities nearby.